HUBUNGAN KARAKTERISTIK FISIK DAN KIMIA BEBERAPA JENIS BUAH MANGGA (Mangifera indica L) TERHADAP PENERIMAAN KONSUMEN - Oksilia Oksilia (Agrium, 2018)
This research aimed  to analyze the relation between physic and chemical  characteristics at three kinds of mango (Mangifera indica L) to consumer preference by using sensoric test. This research method using field randomized design with one factor and sensoric analysis which  color attribute and flavour attribute. The results showed that there was the relation between physic and chemical characteristics of three kinds of mango (Mangifera indica L) to hedonic score of panelis, flavour dan color.